Information Services in School Libraries: A Study of their Contribution to Student Academic Development - Makhmaraimova, Shokhista; Mustafaeva, Noila; Buriyeva, Lobar; Ashirbaeva, Diloram; Kilicheva, Karamat; Rustamova, Manzura; Sapaev, I.B.; Turakulova, Aziza (Indian Journal of Information Sources and Services, 2025)
This research analyses how the information services offered by school libraries impact students' academic development. During this period, when scholarly information is vital, school libraries are being transformed into learning and educational resource centres. This study aims to establish how digital databases, reference books, reading programs, instruction by a librarian, and scaffolding impact students' engagement and comprehension achievement. The study adopted a survey approach. Data was collected using questionnaires and interviews from various schools' students, librarians, and teacher educators to create a complete picture of the existing system. The outcome for school students with functional libraries and active information services is positive, with skill development, reading, and general academic self-esteem. Conversely, the study also points out imbalances with regard to the availability of services in the less funded or more rural components, where school libraries do not have standard facilities. The research shows why the services provided by such libraries need to be equal by measuring the difference and range of such environments. The result is provided with the appropriate policy that needs to be targeted with funds to help improve the library’s aim towards academic achievement for students.